2021
DOI: 10.1016/j.jsps.2020.12.008
|View full text |Cite
|
Sign up to set email alerts
|

What just happened? Impact of on-campus activities suspension on pharmacy education during COVID-19 lockdown – A students’ perspective

Abstract: Introduction COVID-19 pandemic induced lockdown, suspending all on-campus educational activities in the Kingdom of Saudi Arabia (KSA), compelling to continue the education online. We explored pharmacy students’ perspective on its impact on their learning. Methods A Twitter chat was organized on three consecutive days, after final examinations, inviting all pharmacy students in KSA to participate. Day 1 chat included 11 questions regarding learning and assessment, Day 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 24 publications
4
42
0
1
Order By: Relevance
“…In this current study, participants felt that their interactions with academic personnel during online education were not the same as when they were on campus, consistent with Alqurshi (2020) and Mishra et al (2020). A study by Ali et al (2021) also found that their participants felt that their interactions with educators during online education were not the same as when they were on campus. Although technological advancements offer video features that simulate face-to-face interactions, it is unlikely they will never be able to replace real face-to-face interactions.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In this current study, participants felt that their interactions with academic personnel during online education were not the same as when they were on campus, consistent with Alqurshi (2020) and Mishra et al (2020). A study by Ali et al (2021) also found that their participants felt that their interactions with educators during online education were not the same as when they were on campus. Although technological advancements offer video features that simulate face-to-face interactions, it is unlikely they will never be able to replace real face-to-face interactions.…”
Section: Discussionsupporting
confidence: 73%
“…In terms of the qualitative section, many of the comments support the issues raised above and the researcher reemphasises here the importance of the student's voice. Additional skills discovered to manage the online teaching process included virtual classroom experience, patience, empathy, care for students, excellent presentation skills, and proper handling of the teaching-learning tools available with user-friendly features (Ali et al , 2021; Alqurshi, 2020). The importance of face-to-face education cannot be understated, but e-learning can be used in combination with these conventional approaches to offer improved productivity, efficiency and comparative advantage to deliver quality education (Dhawan, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Background: COVID-19 pandemic has affected all walks of life including the education sector (Ali et al, 2021). It is imperative to investigate how pharmacy students perceive their education in the new academic year, the impact of oncampus suspension on learning and the potential long-term effects on their career.…”
Section: Resultsmentioning
confidence: 99%
“…For this, technical support for students and staff is imperative as reported by Almetwazi and his colleagues for their college of pharmacy in Saudi Arabia [ 23 ]. Troubleshooting for faculty staff for the efficient use of LMS has also been emphasized on a global scale [ 24 ]. Our students scored higher in this domain, and this is the reflection of the extra efforts made by our IT department in providing support to our students and the faculty staff.…”
Section: Discussionmentioning
confidence: 99%